The Correspondence between US Secretary of State John Foster Dulles and the Lithuanian Consul in Chicago dr. Petras Povilas Daužvardis - Petraitytė-Briedienė, Asta (History / Istorija, 2022)
Abstract. The article presents the correspondence between US Secretary of State John Foster Dulles and the Lithuanian Consul in Chicago, Dr. Petras Povilas Daužvardis (copies of 14 letters; May 21–November 28, 1952) and the circumstances mentioned in them.